Kamaruddin Amin's Contribution to the Authenticity of the Hadith - Wika Fisepta Septa Tiari Diria Putri; Ida Rochmawati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Research on the historicity of hadith has been strongly influenced by methods developed by non-Muslim scholars, such as matn dating, sanad analysis, hadith codices, and isnad cum matn analysis, which often question the attribution of hadith to the Prophet Muhammad. Scholars like Ignaz Goldziher, Joseph Schacht, and Harald Motzki introduced theories such as common link and argumentum e silentio, leading to skepticism regarding hadith authenticity. This study examines Kamarudin Amin’s critique of these approaches. He argues that dating methods alone cannot serve as a definitive basis for validating or rejecting hadith historicity. Instead, he proposes an integrative approach that combines sanad and matn criticism to achieve a more comprehensive analysis. Kamarudin Amin contends that common links do not necessarily indicate fabrication but reflect systematic transmission processes. He also addresses debates on the justice of the Companions by contextualizing historical events such as the Jamal War and the assassination of ‘Uthman. Through textual reconstruction and variant analysis, this research highlights his contribution to developing an integrative and context-sensitive methodology in hadith studies, reinforcing the relevance of Islamic scholarly traditions in contemporary academic discourse.